2021
DOI: 10.1038/s41467-021-23053-8
|View full text |Cite
|
Sign up to set email alerts
|

Hyperactivation of HER2-SHCBP1-PLK1 axis promotes tumor cell mitosis and impairs trastuzumab sensitivity to gastric cancer

Abstract: Trastuzumab is the backbone of HER2-directed gastric cancer therapy, but poor patient response due to insufficient cell sensitivity and drug resistance remains a clinical challenge. Here, we report that HER2 is involved in cell mitotic promotion for tumorigenesis by hyperactivating a crucial HER2-SHCBP1-PLK1 axis that drives trastuzumab sensitivity and is targeted therapeutically. SHCBP1 is an Shc1-binding protein but is detached from scaffold protein Shc1 following HER2 activation. Released SHCBP1 responds to… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
47
0

Year Published

2022
2022
2025
2025

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 46 publications
(50 citation statements)
references
References 47 publications
(56 reference statements)
3
47
0
Order By: Relevance
“…A previous study showed that SHC1 facilitated the development of bladder cancer [ 6 ]. To gain insight into the subset of SHC1-binding proteins and identify the key factor for accelerating tumor progression, we mapped 32 binding proteins associated with SHC1 according to the findings of Wengui Shi et al [ 7 ] and screened for candidates among 32 genes that were differentially expressed between 19 paired bladder cancer and adjacent nontumor tissues (Fig. 1A, B ).…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…A previous study showed that SHC1 facilitated the development of bladder cancer [ 6 ]. To gain insight into the subset of SHC1-binding proteins and identify the key factor for accelerating tumor progression, we mapped 32 binding proteins associated with SHC1 according to the findings of Wengui Shi et al [ 7 ] and screened for candidates among 32 genes that were differentially expressed between 19 paired bladder cancer and adjacent nontumor tissues (Fig. 1A, B ).…”
Section: Resultsmentioning
confidence: 99%
“…In addition, nuclear translocation of SHCBP1 is a downstream consequence of HER2 activation, which is dependent on phosphorylation of SHCBP1 at the Ser273 site. Blocking HER2 activation using trastuzumab effectively abolished EGF-induced nuclear localization of SHCBP1 in gastric cancer cells [ 7 ]. In our study, we confirmed that upon EGF induction, SHCBP1 translocates to the nucleus, where it binds to RACGAP1 through its N-terminal domain of amino acids 1 ~ 428, and inhibits the GAP activity of RACGAP1 toward RAC1, causing accelerated EGF-induced cell spreading and increased invasiveness of bladder cancer cells.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Notably, it was shown that SHCBP1 was significantly up-regulated in breast cancer tissues, and that SHCBP1 knockout inhibited cell proliferation [ 37 ], thus supporting the hypothesis that SHCBP1 is an oncogene. Recently, it was shown that the overproduction of HER2-SHCBP1-PLK1 diminishes the efficacy of trastuzumab in the treatment of HER2-positive gastric cancer by promoting tumor cell mitosis [ 38 ]. Genes in the DNA replication initiation pathway including ORC6 were shown to have prognostic values for numerous cancers including breast cancer [ 39 , 40 , 41 , 42 , 43 ].…”
Section: Discussionmentioning
confidence: 99%
“…156 Although several HER-2 targeted drugs have entered clinical trials for patients with GC, the FDA has approved only trastuzumab for first-line treatment of patients with advanced GC. [239][240][241] In addition, HER-2-targeted CAR-T cell therapy for GC is increasingly gaining attention to avoid drug resistance and improve treatment outcomes. 241,242 Song et al produced genetically modified human T cells that express HER-2-specific CAR consisting of CD137 and CD3ζ, 156 which not only recognized and killed HER-2 + GC cells in vitro but also showed effective and persistent antitumor activity against HER-2 + GC xenografts in vivo.…”
Section: Advances In Her-2-targeted Car-t Cell Therapy For Gcmentioning
confidence: 99%